The Effect of Work Conflict on Employee Performance: The Moderating Role of Transformational Leadership - Edelin Febriyanti; Puspita Chairun Nisa (International Journal of Economics, Management and Accounting (IJEMA), 2025)
In today's global era, the work environment often faces challenges, one of which is work conflict which can have a negative impact on employee performance. The purpose of this study is to gain a better empirical understanding of the effect of work conflict on employee performance and the role of transformational leadership in moderating work conflict. This study used a purposive sampling technique involving 220 operational staff respondents at a manufacturing company in the Cikarang, Bekasi area. Data analysis used Structural Equation Modeling-Partial Least Square (SEM-PLS). This study produced findings including work conflict having a negative effect on employee performance, then transformational leadership having a positive effect on employee performance, then work conflict having no effect on job satisfaction, and job satisfaction having no effect on employee performance. Further research is expected to expand the scope of the research area and add other variables related to employee performance such as employee engagement.